Cli-fi and class : socioeconomic justice in contemporary American climate fiction - Rosenthal, Debra J., 1964-; Molesky, Jason de Lara, 1985- (University of Virginia Press, 2023)
"The essays in this collection analyze the complex interplays between climate change and inequalities of wealth and power in best-selling popular novels, science fiction titles, literary novels, Hollywood films, and Broadway plays, among other forms"-- Provided by publisher.
Keywords: Climatic changes in literature.; Social justice in literature.; American fiction -- 21st century -- History and criticism.; Climat -- Changements, dans la littérature.; Justice sociale dans la littérature.; Roman américain -- 21e siècle -- Histoire et critique.; Science Fiction & Fantasy.; LITERARY CRITICISM.; Subjects & Themes.; American fiction; Climatic changes in literature; Social justice in literature; 2000-2099; Electronic books.; Criticism, interpretation, etc.